Step-Wise Weight Appraisal Ratio Analysis in the Assessment of Biosurfactant - Balo, Figen; Sua, Lutfu S. (World Scientific Publishing Co., 2023)
Using and consuming healthy and natural products has been of concern for many of us. We want all the products we eat, drink, wear, and use to be natural or healthy, but over the years, it has become either very difficult to find natural products or it can be very expensive. Cleaning our body and kitchen utensils with natural products has also recently emerged as an important issue. In this study, we evaluate washing liquids from the viewpoint of human and environmental health. While making the evaluation, nine important criteria were taken into consideration and six alternative washing liquids were selected to find out which one is more suitable. Multi Criteria Decision Making Methodologies (MCDM) were utilized while performing the ranking process. Criteria weights were found through the Step-wise Weight Appraisal Ratio Analysis (SWARA) methodology. The alternatives’ ranking was determined through the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methodology. © 2023 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Biosurfactant; MCDM; SWARA; TOPSIS; Weight assessment